Analysis of the Implementation of the Minimum Service Standard Policy for Outpatient Care in Hospitals - Maharani, Cintya; Haryono, Bambang Santoso; Hermawan, Hermawan (Universitas Padjadjaran, 2025)
This study examines the implementation of the Minimum Service Standard (MSS) policy for outpatient care at Ngudi Waluyo Regional Hospital, Wlingi, as mandated by Director’s Regulation No. T/T 188/41/409.52/PER/2024 on Public Service Standards. A qualitative case study approach was employed, with data collected through in-depth interviews with 36 informants, direct observations, and document analysis. Data were analyzed using NVivo software. The findings reveal four key factors affecting policy implementation: (1) Unsystematic communication processes; (2) disparities in the distribution of human resources and inadequate maintenance of technological facilities; (3) staff dispositions marked by inconsistencies between commitment and discipline; and (4) complex bureaucratic structures accompanied by uneven understanding among personnel. While community support for the policy was relatively strong, public participation had not yet been fully optimized. Recommended strategies include strengthening internal communication channels, adopting data-driven human resource management, implementing transparent performance systems, simplifying bureaucratic procedures, and fostering adaptive service innovations. This study contributes to the literature on public policy implementation in the health sector, particularly regarding efforts to enhance the quality of outpatient care services.